Effect of styrene addition on polystyrene molecular degradation by Lewis acids - Diaz, Monica Fatima (2009)
The polystyrene molecule can suffer chain scission by beta-cleavage mechanism in the presence of Lewis acids. This is an undesirable secondary reaction, particularly when the Friedel-Crafts alkylation is applied to immiscible polyolefin/polystyrene (PS) blends compatibilization. It competes with the main copolymerization reaction, degrading the PS and impairing the properties of the blend. A simple experimental procedure of styrene (St) addition is proposed to compensate the PS degradation. The effect of St on the chain scission is studied by the PS molecular weight variation and reaction gases evolution. Some hypotheses are worked out to get a basic description of this complex cationic reactive process. © 2009 Wiley Periodicals, Inc.